Improved Inclusive Student Life: Al-Qur'an And Biomechanics Therapy's Combined Positive Competence Enhancement - Munir, Misbahul; Nurmaya, Ika; Hakim, Lukmanul (MSJ : Majority Science Journal, 2025)
A combination of therapies was needed to increase competence in learning for students with special needs. This research aimed to see the effectiveness of a combination of Al-Qur'an and Biomechanical therapy in increasing the competence of inclusive students. This research was conducted using quantitative descriptive methods at SD Muhammadiyah 1 Tulungagung. There were 32 students as respondents who were taken using a purposive sampling technique. The data was collected from interviews and questionnaire responses. The main result of this research is an increase in the competence and quality of life of students with special needs. The conclusion is that there is an increase in the results of quantitative descriptive measurements of learning competence and quality of life after therapy compared to before therapy. These aspects include individuals' Attention to the surrounding environment increased (40.63%), being able to hear or respond when called (43,75%), and being able to carry out commands (78,13%).